Entrepreneurial Sustainability Pathways: Navigating Family Education, Economic Literacy, Innovation Capability, and Entrepreneurial Competence (Empirical Study in Tempe Sanan Industry Village) - Eka Putri Surya; Wening Patmi Rahayu; Titis Shinta Dhewi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The study aims to analyze the influence of economic literacy and family economic education on business sustainability, with innovation capabilities and entrepreneurial competence as mediation variables in Tempe Sanan Industrial Village, Malang City. A quantitative approach was used through an explanatory research method with 158 respondents and SEM-PLS analysis. The results show that economic literacy and family economic education have a significant effect on business sustainability, both directly and through innovation capabilities and entrepreneurial competence. However, the results of the study also found that economic literacy had no effect on the mediating variables of entrepreneurial competence and the variables of entrepreneurial competence could not mediate the influence of economic literacy on business sustainability. These findings underscore the importance of the role of family economic education and economic literacy in shaping sustainable, adaptive, and innovative businesses in the midst of dynamic market competition.